A New 3-D Multistable Chaotic System with Line Equilibrium: Dynamic Analysis and Synchronization - Muhamad Deni Johansyah (Research Collaboration Community (RCC), 2021)
This work introduces a new 3-D chaotic system with a line of equilibrium points. We carry out a detailed dynamic analysis of the proposed chaotic system with five nonlinear terms. We show that the chaotic system exhibits multistability with two coexisting chaotic attractors. We apply integral sliding mode control for the complete synchronization of the new chaotic system with itself as leader-follower systems.